Conciliação medicamentosa de pacientes neurológicos em um hospital universitário do estado do Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
Introduction: Medication reconciliation is a formal and registered process, where the multidisciplinary team prepares a complete, unique and accurate list of all current medications for each patient. From this list, the information is reconciled and compared with the drugs in the medical record, prescription and with the patient's caregivers, during admission, transfer and hospital discharge. The neurological patient is the target of numerous multiprofissional interventions, especially during hospital admissions, where medication conciliation is a strategy that mitigates real and potential adverse events and optimizes pharmacotherapy. There are few studies that reported medication reconciliation data in this group of patients Objective: To identify medication discrepancies, through the medication reconciliation service, in patients admitted to the surgical clinic of a unit specialized in the care of diseases related to the neuromuscular system. Methodology: A descriptive and prospective study was carried out, including patients admitted and followed up by the clinical pharmacy service from September to December 2020. Data were collected through semi-structured interviews with patients, family members and/or caregivers with a review of medical records within 24 - 48 hours of hospital admission on current medication use, in order to develop an up-to-date list of the best possible medication history for comparison with the admission physician's prescription. Differences between home medication use and hospital prescription were defined as discrepancy and classified according to intention and type. Results: After applying the exclusion criteria, 54 patients were included in the study, 28 were female (52%), with a mean age of 46.78 ± 14.50 years, ranging from 19 to 76 years. The total number of patients who reported comorbidities were 25 patients, the most prevalent being pathologies of the circulatory and endocrine systems, with a higher incidence of hypertension (41%). From the accomplishment of the medication conciliation, the use of self-medication predominantly related to drugs of the therapeutic classes of the digestive system and metabolism (42%) and the nervous system (37%) were identified. The use of medicinal plants and herbal medicines was mentioned by 29 patients. Among the medications for continuous use, 35 discrepancies were identified: 20 were intentional (57%), three intentional undocumented (9%) and 12 unintentional (34%). Medication omission was the most common type of discrepancy (86%). Conclusion: Given the above, medication reconciliation proved to be an important resource for identifying discrepancies in the care transition of patients with neurological diseases, especially with regard to medication omission. Thus, this service can be essential for reducing medication errors and the risk of adverse events for patients.
Medication reconciliation of neurological patients in a university hospital in the state of Amazonas
Keywords: Reconciliação de medicamentos; Medicamentos - Administração; Pacientes - Medidas de segurança; Farmácia hospitalar; CIENCIAS DA SAUDE: FARMACIA; Reconciliação de medicamentos; Segurança do paciente; Serviço de farmácia hospitalar; Neurologia